Application of Several Types of Rhizome Powder in Controlling Sitophilus Oryzae L. Pests in Local Siam Mutiara Rice - Rizki Fadila; Riza Adrianoor Saputra; Noor Khamidah (TROPICAL WETLAND JOURNAL, 2020)
Rice is the staple food of the Indonesian population. Siam Mutiara is the preferred local variety of rice in South Kalimantan. Sufficient rice availability must be supported by a rice surplus as food reserves.The main problem with rice storage is the emergence of Sitophilus oryzae L. Therefore it is necessary to control the pest. Non-toxic botanical pesticides can be applied to control S. oryzae. This study aimed to determine the effect of the application of several types of rhizome flour on the mortality rate of S. oryzae, population development of S. oryzae, and weight of Siam Mutiara rice to obtain the most effective rhizome flour. The research was conducted in March 2020 - August 2020 at the Agroecotechnology Production Laboratory, Faculty of Agriculture, Lambung Mangkurat University. The one-factor Completely Randomized Design method (CRD) was used by treating z0 (control/without rhizome powder), z1 (red galangal rhizome powder), z2 (kencur rhizome powder), z3 (red ginger rhizome powder), and z4 (rhizome powder combination). The treatment was repeated 4 times so that there were 20 experimental units. The results showed that the application of red galanus rhizome powder, sling rhizome powder, red ginger rhizome powder, and rhizome powder combination was able to control the population development of S. oryzae and weight damage of Siam Mutiara rice due to S. oryzae pests. The rhizome powder that was most effective in controlling S. oryzae was z1 (red galangal rhizome powder) with a mortality percentage of 32.50%, population of 7 individuals, and rice weight of 99.96%; z2 (kencur rhizome powder) with a mortality percentage of 65%, population of 3 individuals, and rice weight of 99.97%; z3 (red ginger rhizome powder) with a mortality percentage of 62.50, population of 4 individuals, and rice weight of 99.96%; and z4 (rhizome powder combination) with a mortality percentage of 47.50%, population of 5 individuals, and rice weight of 99.95%.